2019
DOI: 10.1017/s0144686x19000515
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in sleep disturbances at retirement: evidence from the Swedish Longitudinal Occupational Survey of Health

Abstract: Although retirement involves a radical change in daily activities, income, social roles and relationships, and the transition from paid work into retirement can, therefore, be expected to affect sleep, little is known about the effects of old-age retirement on changes in sleep disturbances, and how the impact of retirement may vary by gender, age and prior working conditions. This study modelled reported sleep disturbances up to nine years before to nine years following retirement in a sample of 2,110 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 49 publications
2
14
1
Order By: Relevance
“…Longitudinal studies provide consistent evidence that sleep becomes less disturbed and more restorative after retirement (Marquié et al, 2012;Myllyntausta et al, 2018Myllyntausta et al, , 2019Straat et al, 2020;Vahtera et al, 2009). To our knowledge, evidence is still very limited when it comes to how retirement affects specific types of sleep difficulties (e.g.…”
Section: Average Trends In Sleep Difficulties At Retirementmentioning
confidence: 98%
See 3 more Smart Citations
“…Longitudinal studies provide consistent evidence that sleep becomes less disturbed and more restorative after retirement (Marquié et al, 2012;Myllyntausta et al, 2018Myllyntausta et al, , 2019Straat et al, 2020;Vahtera et al, 2009). To our knowledge, evidence is still very limited when it comes to how retirement affects specific types of sleep difficulties (e.g.…”
Section: Average Trends In Sleep Difficulties At Retirementmentioning
confidence: 98%
“…Previous evidence regarding the role of the need to sleep at fixed times and the removal of work-related stressors after retirement is inconsistent. Lower pre-retirement levels of control of working hours and retiring from a full-time job have been associated with larger reductions in sleep difficulties at retirement (Marquié et al, 2012;Straat et al, 2020). Studies have observed associations between lack of work time control (WTC) and sleep disturbances (Salo et al, 2014) but not between WTC and retirement-related reductions in non-restorative sleep (Myllyntausta et al, 2019).…”
Section: The Role Of Work Timing and Stress In Retirement-related Red...mentioning
confidence: 99%
See 2 more Smart Citations
“…Work can impair sleep quality by generating worry and rumination that extend outside of working hours, termed perseverative cognition (Clancy et al, 2020;Harvey et al, 2005;Van Laethem et al, 2018); further, objective sleep quality has been found to be lower on nights before workdays that are expected to be stressful (Petersen et al, 2013). Relief from such stress at retirement may lie behind improvements in post-retirement sleep that are largest for people with high job demands (Vahtera et al, 2009;van de Straat et al, 2019). However, one recent study was unable to observe such effects, concluding that improvements in sleep after retirement are to be explained by mechanisms other than the stress release hypothesis (Myllyntausta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%